Does augmented reality augment user affordance? The effect of technological characteristics on game behaviour. Issue 11 (18th August 2022) - Shin, Donghee
ABSTRACT: This study conceptualises a framework of technological affordances for augmented reality games (ARG) relative to the affordances of internalised and embodied experiences by users. This study examines players' affordances and investigate how they influence user experience in ARG. It explores how affordances are perceived and enacted by users in an augmented environment to maximise user experience of ARG. A multimethod research approach was utilised that integrated ethnographic and statistical methods. Qualitative study confirmed the general structure of affordance framework, while also revealing relational structures with other variables to explore. Based on the affordance factors identified from the ethnographic methods, a survey questionnaire was created to map and investigate the effects of affordance on the user's cognitive processes and the influence of affordance on the gameplay process. The results show that technological properties of the ARG system affect opportunities for action available in the environment (affordances). The heuristic role of immersion and presence affordances through underlying cues appear to trigger a player's sensory representations of affective affordances.